REPOSITIONING TEACHING LEARNING ATTITTUDES IN INSTITUTIONAL CONTEXTS AS AN APPROACH TO TECHNOLOGICAL INTERVENTION IN EDUCATION - S. Sailaja Radhakrishna (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Technological interventions for better educational outcomes are well considered notions in the present educational contexts. While teacher training and provision of technological services affirm the ushering in of change, the rural contexts continue to have apprehensions of learning English coupled with the use of technology. Incremental changes requiring far greater adjustments in teaching and learning attitudes are required to formulate an approach to bring in technological intervention.